Qui Judicatis Terram: An exploration of John Ruskin’s ideas on ‘inequality’ - Carvalho, L. (20th Annual Conference of the European Society for the History of Economic Thought, Paris., 2016)
This paper provides a close look at the views on socio-economic inequality advanced by John Ruskin (1819-1900), namely as deployed in his major politico-economical work, Unto This Last, with a particular focus on its second and third essays, respectively The Veins of Wealth and Qui Judicatis Terram. For Ruskin, inequalities must be assessed in terms of Justice in behaviours regarding the ‘the mode of acquisition’ and the responsible ‘use’ of riches. Ruskin´s proposals to address ‘unjust’ behaviours are also discussed, stressing the centrality of individual change through the development of a consumption ethics and a business ethics.